Heteronanowires of MoC–Mo2C as efficient electrocatalysts for hydrogen evolution reaction. Issue 5 (19th February 2016) - Lin, Huanlei; Shi, Zhangping; He, Sina; Yu, Xiang; Wang, Sinong; Gao, Qingsheng; Tang, Yi
Abstract : MoC–Mo2 C heteronanowires accomplished via controlled carbonization are efficient in the hydrogen evolution reaction due to a synergistic enhancement. Abstract : Exploring efficient noble-metal free electrocatalysts for the hydrogen evolution reaction (HER) is one of the most promising pathways for facing the energy crisis. Herein, MoC–Mo2 C heteronanowires composed of well-defined nanoparticles were accomplished via controlled carbonization, showing excellent HER activity, fast kinetic metrics and outstanding stability in both acid and basic electrolytes. In particular, the optimal one consisting of 31.4 wt% MoC displayed a low overpotential ( η 10 = 126 and 120 mV for reaching a current density of −10 mA cm −2 ), a small Tafel slope (43 and 42 mV dec −1 ) and a low onset overpotential (38 and 33 mV) in 0.5 M H2 SO4 and 1.0 M KOH, respectively. Such prominent performance, outperforming most of the current noble-metal free electrocatalysts, was ascribed to the carbide surface with an optimized electron density, and the consequently facilitated HER kinetics. This work elucidates a feasible way toward efficient electrocatalysts via heteronanostructure engineering, shedding some light on the exploration and optimization of catalysts in energy chemistry.